2021
DOI: 10.1002/car.2671
|View full text |Cite
|
Sign up to set email alerts
|

What Helps? Mothers' and Children's Experiences of Community‐Based Early Intervention Programmes for Domestic Violence

Abstract: Early help or early intervention is increasingly recommended for safeguarding children living with domestic violence, but little is known about what is effective. This article discusses findings from an evaluation of a pioneering early help service in North West England. This new service aimed to improve the safety and wellbeing of families (mothers and children) who were assessed as below the level of ‘high risk’ domestic violence and below the threshold for a child protection order. Between January 2014 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…This emphasises the need to improve oral health practitioners’ understanding in detecting CAN cases in early stages, provide the necessary support to children and their families, and report to the child protection agencies to provide safer environments to children and adolescents in need. Despite challenges to measuring the impact of early intervention approaches on child protection, McCarry et al [ 38 ] identified a perceived need and positive impact of the early interventions approach by children, mothers, and service providers to effectively safeguard children from family violence. Emphasising the need for evidence-based early intervention approach to prevent further harm to the child is equally crucial to detecting and reporting potentially imminent harm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This emphasises the need to improve oral health practitioners’ understanding in detecting CAN cases in early stages, provide the necessary support to children and their families, and report to the child protection agencies to provide safer environments to children and adolescents in need. Despite challenges to measuring the impact of early intervention approaches on child protection, McCarry et al [ 38 ] identified a perceived need and positive impact of the early interventions approach by children, mothers, and service providers to effectively safeguard children from family violence. Emphasising the need for evidence-based early intervention approach to prevent further harm to the child is equally crucial to detecting and reporting potentially imminent harm.…”
Section: Discussionmentioning
confidence: 99%
“…The guideline should provide information on how DTs and OHTs can support the family and the community, not just detecting and reporting the potential CAN cases. Providing necessary support helps as a part of holistic care to the family and the community across the continuum of needs that can protect children and adolescents from further harm from CAN [ 38 ]. The government recently introduced Te Aorerekura (the national strategy to eliminate family violence and sexual violence), which includes a reformation of NZ healthcare to make it more equitable and better suited to meet the needs of all people [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pernebo and Almqvist (2016) noted that young children in group counselling considered social workers trustworthy if they appeared well-intentioned and responsible. Similarly, other studies found that children perceived social workers as trustworthy when they were supportive and helpful (Callaghan et al, 2019;Coburn & Gormally, 2014;McCarry et al, 2021). The level of trust may impact their willingness to disclose sensitive information: "being in a trusting environment enabled participants to express themselves, and to disclose things that they had not previously felt able to discuss" (Callaghan et al, 2019 p. 530).…”
Section: Trustmentioning
confidence: 96%
“…Pernebo and Almqvist (2016) emphasized that a sense of security could be further enhanced by a predictable environment, such as meeting in the same room with the same furniture. Furthermore, McCarry et al (2021) found that meeting in a school environment, which was not the children's own school in all cases, was appreciated by some of the children. Therefore, the physical environment where children meet social workers can enhance their sense of security in various ways.…”
Section: A Safe Spacementioning
confidence: 99%
“…Early help or early intervention can promote resilience and reduce risks and is increasingly being recommended to safeguard children. The next paper in this issue by Melanie McCarry from the University of Strathclyde and colleagues from the University of Central Lancashire (McCarry et al, 2021) reports on an evaluation of early intervention services running in the North West of England for women and children suffering DV. The new early help services were part of the Safer Together consortium that involved eight organisations providing a range of specialist DV services including a refuge, helpline, outreach and a DV advocacy service.…”
Section: 'The Reduced Opportunities For Preventative Work By Health Visitors With Children and Families Is A Significant Concern'mentioning
confidence: 99%